Absolute and relative strength performance following creatine monohydrate supplementation combined with periodized resistance training - Syrotuik, D. G.; Bell, G. J.; Burnham, R.; Sim, L. L.; Calvert, R. A.; McLean, I. M. (The Journal of Strength and Conditioning Research, 2000)
Twenty-one men (20-26 years old) were randomly assigned to one of 3 groups: an acute creatine monohydrate (Cr) 5-day load and maintenance placebo (AL); an acute Cr 5-day load and 32-day maintenance dose (ALM), and a placebo group (PL). The AL and ALM roups received Cr dissolved in a flavored drink at a dosage of 0.3g·kg1·d1 for 5 days for the acute load and the ALM group ingested Cr at 0.03g·kg1·d1 for the maintenance phase. The PL group ingested the drink only. While supplementing, all groups participated in a periodized resistance training program performing the same relative load and volume of training regardless of their assigned experimental group. Bench press (BP) and incline leg press (ILP) absolute strength (1 repetition maximum [1RM]), total lifting volume (80% of 1RM to failure), and strength per mass ratio were assessed initially (T1), after a 5-day acute load (T2), and following the 32-day maintenance phase (T3). No differences were observed in 1RMs, total lifting volume, or strength per mass ratio between experimental groups over time except in the AL group, which showed a significant improvement in the total lifting volume for BP after the acute Cr load. All groups significantly improved 1RM, total lifting volume, and strength per mass ratio from T1 to T3, with no changes observed from T1 to T2 in BP and ILP. The findings suggest that Cr supplementation combined with resistance training when relative loads and volumes are the same as a placebo group does not result in a training advantage in absolute or relative strength performance.